Dual TGFβ/BMP pathway inhibition enables expansion and characterization of multiple epithelial cell types of the normal and cancerous breast. - Prasad, Mayuri (Mol Cancer Res, 2019)
Functional modeling of normal breast epithelial hierarchy and stromal-epithelial cell interactions have been difficult due to inability to obtain sufficient stem-progenitor-mature epithelial and stromal cells. Recently reported epithelial reprogramming assay has partially overcome this limitation, but cross contamination of cells from the feeder layer is a concern. The purpose of this study was to develop a feeder-layer independent inexpensive method to propagate multiple cell types from limited tissue resources. Cells obtained after enzymatic digestion of tissues collected at surgery or by core-needle biopsies were plated on tissue culture dishes pre-coated with laminin-5-rich conditioned media from the rat bladder tumor cell line 804G and a defined growth media with inhibitors of ROCK, TGFβ, and BMP signaling. Cells were characterized by flow cytometry, mammosphere assay, 3D cultures, and xenograft studies. Cells from the healthy breasts included CD10+/EpCAM- basal/myoepithelial, CD49f+/EpCAM+ luminal progenitor, CD49f-/EpCAM+ mature luminal, CD73+/EpCAM+/CD90- rare endogenous pluripotent somatic stem, CD73+/CD90+/EpCAM-, Estrogen Receptor alpha (ERα)-expressing ALCAM (CD166)+/EpCAM+, and ALDFLUOR+ stem/luminal progenitor subpopulations. Epithelial cells were luminal (KRT19+), basal (KRT14+) or dual positive luminal/basal hybrid cells. While breast cells derived from BRCA1, BRCA2, and PALB2 mutation carriers did not display unique characteristics, cells from women with breast cancer protective alleles showed enhanced differentiation. Cells could also be propagated from primary tumors and metastasis of breast, ovarian, and pancreatic cancer-neuroendocrine subtype. Xenograft studies confirmed tumorigenic properties of tumor-derived cells.